2003
DOI: 10.1007/s00125-003-1067-y
|View full text |Cite
|
Sign up to set email alerts
|

T130I mutation in HNF-4α gene is a loss-of-function mutation in hepatocytes and is associated with late-onset Type 2 diabetes mellitus in Japanese subjects

Abstract: Aims/hypothesis. Mutations in hepatocyte nuclear factor (HNF)-4α gene cause a form of maturity-onset diabetes of the young (MODY1). The T130I mutation is a rare missense mutation, which affects a conserved amino acid in a DNA binding domain. This mutation can be found in the general population, so this variant alone does not cause MODY. However, its significance in the development of late-onset Type 2 diabetes is not known. Methods. We screened 423 unrelated Japanese patients with late-onset Type 2 diabetes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 43 publications
6
38
2
Order By: Relevance
“…The second SNP Thr130Ile is a rare variant that was previously described, is located in the DNA-binding domain and has been associated with reduced function in hepatocyte cell lines as well as higher incidence of maturity onset diabetes mellitus and lower HDL cholesterol. 25,31 This SNP was present at a low allele frequency of 1% in our study population; therefore, any potential effect on drug pharmacokinetics or pharmacodynamics could not be determined.…”
Section: Discussionmentioning
confidence: 96%
“…The second SNP Thr130Ile is a rare variant that was previously described, is located in the DNA-binding domain and has been associated with reduced function in hepatocyte cell lines as well as higher incidence of maturity onset diabetes mellitus and lower HDL cholesterol. 25,31 This SNP was present at a low allele frequency of 1% in our study population; therefore, any potential effect on drug pharmacokinetics or pharmacodynamics could not be determined.…”
Section: Discussionmentioning
confidence: 96%
“…The T130I variant, which affects a residue in the DNA binding region, is thought to be a polymorphism because this missense mutation is found in 0-5% of nondiabetic Caucasians [17,19] and insulin and C-peptide secretion is unaltered in healthy carriers [19]. A recent Japanese study [20] suggested that the T130I variant might be associated with lateonset type 2 DM in Japanese subjects because it is found more frequently in type 2 DM patients than in the general population (3.5% versus 0.8%) and it is associated with loss of function in hepatocytes. However, this study maintained that the T1301 variant's significance in the development of type 2 DM needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These genes play a role in the development of the liver, in the regulation of hepatic metabolic functions, and in the development and functioning of beta cells. Variants in these genes that do not lead to MODY have been found to be associated with decreased insulin secretion and an increase in the risk of T2D in various populations, but as with other candidate genes, their role in worldwide diabetes prevalence appears to be relatively small [36][37][38] .…”
Section: Wfs-1 : Wfs-1 Gene Encodes Wolframin a Protein Thatmentioning
confidence: 99%